Transforming Teacher Performance Through School Management Digitalization And Data-Based Discipline Systems At Smp Negeri 03 Limboto Barat - Nina Lamatenggo; Intan Abdul Razak; MAMAT ABAS; Wiwit Zuriati Uno (Cv. Kayaswara, Indonesia, 2025)
This study aims to analyze how digital school management and data-driven discipline systems contribute to improving teacher performance at SMP Negeri 03 Limboto Barat. A descriptive qualitative method was employed, involving interviews, observations, and document analysis to explore teachers’ experiences and the school’s implementation processes. The findings reveal that digitalization strengthened accountability, enhanced consistency in teachers’ work behavior, and improved the efficiency of administrative tasks. Teachers became more disciplined, more responsive to their professional responsibilities, and more consistent in fulfilling instructional requirements. The digital system also enabled more objective supervision and supported evidence-based decision-making within the school. Overall, the study shows that digital transformation not only improves internal school governance but also provides insights into effective performance management practices relevant to broader organizational and managerial contexts.